COMPARISON OF THE EFFECTIVENESS OF METHODS FOR BONE MARROW HARVESTING FROM NON-HEART BEATING DONORS - M. Sh. Hubutija; I. N. Ponomarev; N. V. Borovkova (Вестник трансплантологии и искусственных органов)
Aim. To compare the effectiveness of different methods for bone marrow (BM) harvesting from non-heart beating donors taking into account the number and the quality of collected hematopoietic stem cells (HSC). Materials and methods. The study was performed on 43 non-heart beating donors. For BM harvesting two bone marrow aspiration needles were installed in each iliac bone. The needles were installed in one bone connected to closed system, combined with surgical suction and volumetric pump. BM aspiration was performed using different values for vacuum and combining with perfusion solution into the bone. The volume, the number of nucleated cells (NC), HSC and cell viability were evaluated in the obtained samples. Results. Compared with the standard mode the usage of vacuum 0.6–0.7 atm increased the collection of NC by 65.6%, HSC 87%, and did not reduce their viability. Using a vacuum of 0.9 atm reduced the amount of collected HSC and damaged cells. While using combined aspiration and perfusion of BM HSC were prepared at more than 86.2%, but the viability of the cells was lower than under the standard aspiration. Having coherently performed a standard aspiration and aspiration with perfusion from one iliac bone 407.2 ± 46.7 ml BM, 8.0 ± 0.8 × 109  NC and 194.2 ± 20.8 × 106  HSC were harvested. The proportion of viable cells was not less than 75.2 ± 3.2%. Conclusion. Method of BM harvesting implying coherently performing aspiration and aspiration-perfusion with the usage of vacuum 0.6–0.7 atm allows to prepare more progenitor cells without losing their quality. As a result, from one non-heart beating donor different types of progenitor cells can be collected in the amount sufficient for systemic infusion in adult patient.